2011
DOI: 10.1007/s13593-011-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sensitivity to paraquat evolves under selection with low glyphosate doses in Lolium rigidum

Abstract: This is the first report of low-dose glyphosate selection causing a shift towards paraquat resistance. Herbicide resistance in weed species is a serious threat to world agriculture. We report rapid resistance evolution in the genetically variable cross-pollinated grass weed Lolium rigidum when recurrently selected with low doses. Results show that an herbicide-susceptible L. rigidum population selected over three generations with below-label doses of glyphosate exhibited not only glyphosate resistance evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…3; Table 4). The evolution of pyroxasulfone resistance, evidenced here by low‐dose pyroxasulfone selection, is similar to other examples of rapid resistance evolution experimentally observed in L. rigidum (Neve & Powles, 2005a,b; Busi & Powles, 2009, 2011; Manalil et al. , 2011).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…3; Table 4). The evolution of pyroxasulfone resistance, evidenced here by low‐dose pyroxasulfone selection, is similar to other examples of rapid resistance evolution experimentally observed in L. rigidum (Neve & Powles, 2005a,b; Busi & Powles, 2009, 2011; Manalil et al. , 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Studies with Lolium rigidum (Gaud.) have shown that recurrent low‐dose herbicide selection can lead to rapid and substantial herbicide resistance evolution (Neve & Powles, 2005a; Busi & Powles, 2009, 2011; Manalil et al. , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with the highly genetically variable, cross‐pollinated and resistance‐prone grass weed species Lolium rigidum (Gaud.) have established that recurrent selection at low herbicide dose can rapidly lead to herbicide resistance evolution . Obligate cross‐pollination in L. rigidum ensures that with low‐dose herbicide selection the genetic traits conferring survival will be shared through cross‐pollination, and herbicide resistance will evolve .…”
Section: Introductionmentioning
confidence: 99%
“…and rigid ryegrass (Lolium rigidum Gaud.) are known for their genetic diversity and biotypes with resistance to several different herbicide modes of action have been reported (Falk et al 2005;Nordby et al 2007;Stachler and Loux 2007;Norsworthy et al 2008;Busi and Powles 2011;Heap 2011). The repeated use of glyphosate in an intensive GR cropping system has led to the selection of several GR weed biotypes worldwide (Heap 2011).…”
mentioning
confidence: 99%